Ataxia telangiectasia mutated and Rad3 related (ATR) protein kinase inhibition is synthetically lethal in XRCC1 deficient ovarian cancer cells - Sultana, Rebeka; Abdel-Fatah, Tarek; Perry, Christina; Moseley, Paul; Albarakti, Nada; Mohan, Vivek; Seedhouse, Claire; Chan, Stephan; Madhusudan, Srinivasan (Public Library of Science, 2013)
Introduction Ataxia telangiectasia mutated and Rad3 Related (ATR) protein kinase is a key sensor of single-stranded DNA associated with stalled replication forks and repair intermediates generated during DNA repair. XRCC1 is a critical enzyme in single strand break repair and base excision repair. XRCC1-LIG3 complex is also an important contributor to the ligation step of the nucleotide excision repair response.